1989
DOI: 10.1111/j.2042-3306.1989.tb02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscular adaptation of horses during intensive training and detraining

Abstract: Five horses were studied during a five-week regime of controlled intensive daily training on a high-speed treadmill followed by five weeks of detraining. Muscle biopsies were taken weekly from both the right and left gluteus muscle and from the sternocephalicus muscle before, and at the end of, the training and detraining periods. Histochemical and biochemical analyses of the sternocephalicus muscle showed no metabolic adaptation with either training or detraining. No significant differences were observed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 24 publications
3
33
2
2
Order By: Relevance
“…Most studies investigating training in horses have shown few if any changes in fibre area in response to the training stimulus [9,10,16]. The increased fibre area in all fibre types during the high-intensity phase of training (phase 2) in the current study indicates that high-intensigram in horses [10].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Most studies investigating training in horses have shown few if any changes in fibre area in response to the training stimulus [9,10,16]. The increased fibre area in all fibre types during the high-intensity phase of training (phase 2) in the current study indicates that high-intensigram in horses [10].…”
Section: Discussionmentioning
confidence: 69%
“…Studies investigating skeletal muscle adaptations to training in horses have found up to twofold increases in aerobic enzyme activity [9,10,15,16,19,26] and increases in capillarisation of muscle [17]. Straub et al [33] have found an increase in volume density of mitochondria after 4 weeks of training in horses.…”
Section: Introductionmentioning
confidence: 98%
“…This suggests that horses are well adapted to rely on fat metabolism and aerobic energy supply at rest, but probably also during exercise. The adaptation to, and importance of, aerobic substrate utilisation during exercise in Thoroughbred and Standardbred horses has been documented in a number of studies (Lindholm and Piehl, 1974;Wilson et al, 1987;Essé n-Gustavsson et al, 1989) and is also confirmed by the correlation between the performance of Standardbred horses and plasma lactate threshold (V La4 ) (Persson, 1983). Equine muscle also shows high plasticity with respect to its adaptation to energetic demands as a result of exercise training (Voiton et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
“…It is well known that skeletal muscle of well-trained horses have high type IIA/IIB ratios, oxidative capacities and capillary supplies (Essén-Gustavsson and Lindholm 1985;Essén-Gustavsson et al 1989;Karlström et al 1991). The gluteus medius muscle of HV horses has previously been analysed histochemically and compared to muscle of NV horses.…”
Section: Introductionmentioning
confidence: 99%